Differences in the three swimming style learning outcomes from gender - Syahrastani Syahrastani (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This research was conducted because swimming style learning outcomes are still weak in terms of gender. This study aims to determine the interaction between gender and swimming style learning outcomes. This type of research is quasi-experimental using a 2x3 factorial design. The research method used is descriptive-comparative, with a sample of 100 sports education students. The questionnaire is an effective data collection method to test the variables to be measured and the answers expected by the respondents. The questionnaire applies a Likert scale by providing an opportunity to answer each item. Hypothesis testing was carried out with the SPSS 22.0 program using one-way ANOVA, and two-way ANOVA analysis. The results showed that (1) there were differences in the learning outcomes of swimming style in terms of gender, (2) there was an interaction between gender and swimming style. The learning outcomes of male students' swimming styles were higher than female students, both in the breaststroke, butterfly, and freestyle.